Comparative Study of Light-Dark Patterns on CDs (Compact Disks) and Leek Stems as Simple Gratings in Diffraction Grating Practicals - Farah Amara Valio; Annisa Nurul Amalia; Hilwa Syamila Haq; Ahmad Suryadi; Fuji Hernawati Kusumah (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2024)
Physics learning often faces a lack of available learning media because it is difficult to obtain or the price is expensive, one example is the diffraction grating practicum. This research tries to improve the limitations of physics learning media, especially in diffraction grating practicum. The use of materials that are more affordable and easy to find, namely leek stems and CD (Compact Disk) as diffraction gratings is an innovative effort for teachers and students to overcome the lack of availability and expensive practical equipment. This research uses experimental methods and aims to compare the light-dark patterns produced by by the two types of grid, namely the leek stem grid and the CD grid. The results of the research show that the light-dark pattern formed from the CD grid has a clearer pattern than the leek stem grid. The distance between the dark and light patterns produced by the CD grid is(15±0,05)×10^(-2)m, while the value for the leek grid is (7±0,05)×10^(-2)m. Thus, it can be concluded that the use of CD chips grid are more efficiently than the use of grids on leek stems as gratings in diffraction grating practice. This innovation provides a concrete solution to the constraints of availability and cost of practical equipment. This allows teachers and students to conduct experiments with more affordable resources. This research not only demonstrates the efficiency of CDs as diffraction gratings, but also contributes to the development of more practical and economical physics learning methods.